An amino-decorated NbO-type metal–organic framework for high C2H2 storage and selective CO2 capture1. Issue 94 (14th October 2015) - Cai, Jianfeng; Wang, Huizhen; Wang, Hailong; Duan, Xing; Wang, Zhiyu; Cui, Yuanjing; Yang, Yu; Chen, Banglin; Qian, Guodong
<x xml:space="preserve">Abstract</x> A novel amino-decorated NbO-type metal–organic framework (ZJU-8) has been designed and synthesized, exhibiting high acetylene storage and selective CO2 capture and separation capacities at room temperature.